2010
DOI: 10.1161/circgenetics.109.898569
|View full text |Cite
|
Sign up to set email alerts
|

A Common Single Nucleotide Polymorphism Can Exacerbate Long-QT Type 2 Syndrome Leading to Sudden Infant Death

Abstract: Background-Identification of infants at risk for sudden arrhythmic death remains one of the leading challenges of modern medicine. We present a family in which a common polymorphism (single nucleotide polymorphism) inherited from the father, combined with a stop codon mutation inherited from the mother (both asymptomatic), led to 2 cases of sudden infant death. Methods and Results-KCNQ1, KCNH2, SCN5A, KCNE1, KCNE2, CACNA1c, CACNB2b, and KCNJ2 genes were amplified and analyzed by direct sequencing. Functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 43 publications
2
45
1
Order By: Relevance
“…A similar interaction between KCNH2 p.K897T (inherited from the father) and a LQTS mutation (KCNH2 p.P926AfsX14 inherited form the mother) was identified in a sudden infant death syndrome (SIDS) case. In this case heterologous co-expression of the nsSNP KCNH2 p.K897T and the mutation p.P926AfsX14 led to loss of function of the HERG current which was much greater than expression of KCNH2 p.K897T or KCNH2 p.P926AfsX14 alone [22,24]. In agreement with these results, but in sharp contrast with those from Bezzina and Zhang, Barsheshet Modulates activation and inactivation [38] SCN5A-p.S1103Y 2.5 c SCN5A-p.R680H 3.6 fold increase of Late INa [39] et al [25] in a cohort study (n = 218) on genotype-negative LQTS patients (no identified LQT1/2/3 mutation) showed that KCNH2 p.K897T was associated with a 11-fold (P < 0.001) increase in the risk of syncope.…”
Section: The Additive Effect Of Multiple Mutationssupporting
confidence: 82%
“…A similar interaction between KCNH2 p.K897T (inherited from the father) and a LQTS mutation (KCNH2 p.P926AfsX14 inherited form the mother) was identified in a sudden infant death syndrome (SIDS) case. In this case heterologous co-expression of the nsSNP KCNH2 p.K897T and the mutation p.P926AfsX14 led to loss of function of the HERG current which was much greater than expression of KCNH2 p.K897T or KCNH2 p.P926AfsX14 alone [22,24]. In agreement with these results, but in sharp contrast with those from Bezzina and Zhang, Barsheshet Modulates activation and inactivation [38] SCN5A-p.S1103Y 2.5 c SCN5A-p.R680H 3.6 fold increase of Late INa [39] et al [25] in a cohort study (n = 218) on genotype-negative LQTS patients (no identified LQT1/2/3 mutation) showed that KCNH2 p.K897T was associated with a 11-fold (P < 0.001) increase in the risk of syncope.…”
Section: The Additive Effect Of Multiple Mutationssupporting
confidence: 82%
“…'The first study to convincingly establish a causal role for a common SNP in a long QT gene in determining the severity of a LQTS phenotype' [18] was the one published in 2005, in which we provided evidence that the KCNH2-K897T polymorphism was able to modify the clinical expression of a latent LQT2 mutation [19]. Very recently, this observation was confirmed by Nof et al [20] in another LQT2 family in which the KCNH2-K897T markedly accentuated the loss of function of mildly defective human ether-a-go-go-related gene (HERG) channels, leading to LQTS-mediated arrhythmias and sudden infant death. Whether the effect of the K897T is limited to some KCNH2 mutation or to all LQT2/LQTS patients still needs to be defined in large populations of LQTS patients.…”
Section: Channelopathiessupporting
confidence: 53%
“…Our present work highlights the importance of using splicing-competent hERG constructs in the characterization of LQT2 PTC mutations. To date, several LQT2 nonsense and frameshift mutations have been analyzed using cDNA constructs under the assumption that PTC mutations would generate truncated hERG channels (Choe et al, 2006; Christé et al, 2008; Gong et al, 2004; Li et al, 1997; Nof et al, 2010; Paulussen et al, 2005; Trudeau et al, 2011). However, based on the 3’-boundary identified in the present study, all of these PTC mutations are expected targets of NMD.…”
Section: Discussionmentioning
confidence: 99%